OPTIMALISASI PENDISTRIBUSIAN GAS LPG PT. SEULAWAH INONG MALANG DENGAN ALGORITMA ACS-RVND PADA HFVRPTW - Elzyn Erianti Zevanya; Sapti Wahyuningsih (MATHunesa: Jurnal Ilmiah Matematika, 2026)
Seulawah Inong faces challenges in managing the distribution process so that LPG gas deliveries can be made on time with minimal operational costs. The main challenge lies in determining an efficient distribution route, given the limited vehicle capacity, differences in costs and heterogeneous fleet capacity, and delivery time constraints, in accordance with the characteristics of the Heterogeneous Fleet Vehicle Routing Problem with Time Windows (HFVRPTW). This study aims to optimally solve this problem by utilizing the Ant Colony System with Randomized Variable Neighborhood Descent (ACS-RVND) algorithm application on the Heterogeneous Fleet Vehicle Routing Problem with Time Windows (HFVRPTW). The results show that with the use of 10 ants, the algorithm successfully generated five optimal distribution routes, with a total distance of 66.11 km, a total service time of 1,242.72 minutes, and a total operational cost of Rp 76,026.5 Keywords: Gas distribution, Route optimization, HFVRPTW, ACS-RVND Algorithm.